Seleksi Genotipe Kedelai (Glycine max L. Merril) untuk Ketahanan terhadap Penggerek Polong Kedelai, Etiella zinckenella Treitschke (Lepidoptera: Pyralidae) - Pasaribu, Febrio; Salbiah, Desita (Jurnal Agro Teknologi Tropika, 2017)
This study was intended to determine soybean genotypes which resistant to soybean pod borer (Etiella zinckenella Treitschke) in Riau. A field experiment was established by randomized complete block design where six cultivars of soybean including Gema, Grobogan, Kaba, Willis, lines KM 19 and KM 25 are planted in plots of 2.5 m in length and 2 m in wide. The parameters observed the number of larva pest per plant, percentage of damage pods per plant, percentage of damage seeds per plant, number of pods per plant, number of seeds per plant, and yield per m2. The data were then analyzed by using analysis of variance and then performed Duncan new multiple range test at 5% level. The results showed the differences among genotypic in the level of resistance to pod borer with variations between moderately resistant to moderately susceptible. Genotype KM 19 and Willis were soybean genotypes that were more resistant to soybean pod borer, Â E. zinckenella Treitschke as indicated by low percentage of pods and seeds attacked. Selection index calculated also showed that genotype KM 19 and Willis had lower value of selection index compared to other genotypes.Â This study implied that both Wilis and KM 19 were potential to be used as parental genotipes in a plant breeding program to develop resistant genotypes to soybean pod borer.